2020
DOI: 10.1038/s41416-020-0905-8
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib is effective against neuroblastoma in vitro and in vivo and inhibits the RAS/MAPK, PI3K/Akt/mTOR and Fos/Jun pathways

Abstract: Background Regorafenib is an inhibitor of multiple kinases with aberrant expression and activity in neuroblastoma tumours that have potential roles in neuroblastoma pathogenesis. Methods We evaluated neuroblastoma cells treated with regorafenib for cell viability and confluence, and analysed treated cells for apoptosis and cell cycle progression. We evaluated the efficacy of regorafenib in vivo using an orthotopic xenograft model. We evaluated rego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…Inhibition of YAP1 (hippo signaling) resulted in RAS-driven NB cells being sensitized to trametinib MEK1/2 and in enhanced G1/S cell-cycle arrest [ 138 ]. Regorafenib, which is known to inhibit the RAS/MAPK, PI3K/Akt/mTOR, and Fos/Jun pathways, has also shown good in vivo and in vitro efficacy against NB cells [ 139 ].…”
Section: Ras-mapk Inhibitors In Clinicsmentioning
confidence: 99%
“…Inhibition of YAP1 (hippo signaling) resulted in RAS-driven NB cells being sensitized to trametinib MEK1/2 and in enhanced G1/S cell-cycle arrest [ 138 ]. Regorafenib, which is known to inhibit the RAS/MAPK, PI3K/Akt/mTOR, and Fos/Jun pathways, has also shown good in vivo and in vitro efficacy against NB cells [ 139 ].…”
Section: Ras-mapk Inhibitors In Clinicsmentioning
confidence: 99%
“…In parallel, Zhang et al [59] characterized the effect of another RET inhibitor, cabozantinib (XL184), on in vitro and in vivo neuroblastoma paradigms. Subsequent studies from the same group found comparable results when using the small-molecule RET/ multikinase inhibitor RXDX-105 [60] or the RET/multikinase inhibitor regorafenib (BAY 73-4506) [61]. Notably, the effect of regorafenib on in vitro and in vivo neuroblastoma models had been previously reported by Chen et al [62].…”
Section: Retmentioning
confidence: 61%
“…For example, FSCN1 was reported to promote HCC cellular proliferation, migration, and invasion, inhibit HCC cellular apoptosis, and increase HCC cellular doxorubicin resistance (55)(56)(57)(58). PI3K/AKT pathway is the classically oncogenic pathway, which has been documented to modulate cell proliferation, survival, and motility in various malignancies (59)(60)(61)(62). PI3K/AKT pathway was also revealed to be the critical downstream target of FSCN1 (51).…”
Section: Discussionmentioning
confidence: 99%